Digital Media Engagement and ADHD: Balancing Risks and Opportunities for Symptom Management - Catama, Bryan V (International Journal of Rehabilitation and Special Education (IJRSE), 2024)
Attention Deficit Hyperactivity Disorder (ADHD) affects many children and adolescents, characterized by inattention, hyperactivity, and impulsivity. The rise of digital media has raised concerns about its impact on ADHD symptoms. This narrative review examines both the risks and benefits of digital media engagement on ADHD symptoms, focusing on attention, hyperactivity, impulsivity, sleep patterns, and social interactions. Children with ADHD tend to engage more with fast-paced and interactive content, potentially worsening attention deficits and impulsivity. However, structured educational apps can improve attention and learning outcomes. Excessive screen time, especially before bed, is linked to poor sleep quality, exacerbating ADHD symptoms. While social media offers positive interactions, overuse may lead to social withdrawal. The review emphasizes a balanced approach to digital media, highlighting the importance of parental monitoring and structured usage. It provides practical guidance for parents, educators, and clinicians, and calls for further research and interventions to maximize digital media’s positive effects while minimizing its negative impacts on ADHD.